Rice Tolerance to Saflufenacil in Clomazone Weed Control Program - E. R. Camargo; S. A. Senseman; G. N. McCauley; J. B. Guice (International Journal of Agronomy)
This research was conducted to evaluate (1) rice tolerance to saflufenacil applied preemergence (PRE) and postemergence (POST) and (2) the combination of saflufenacil and clomazone in light-textured soils. No injury from PRE application of saflufenacil was observed in 2009, and minimal injury for saflufenacil alone was observed in 2010. Injury as high as 68% was observed with combinations of 505 g ha−1 of clomazone applied PRE and 50 g ha−1 of saflufenacil applied POST in 2009 early evaluations. No interaction between clomazone and POST saflufenacil rates was observed in 2010. Rice injury intensified with increasing rates of saflufenacil applied POST. However, rice recovered with time for herbicide treatments applied PRE and POST in both years. Consequently, rice yield was not affected by any of the saflufenacil rates applied either PRE or POST in a clomazone weed control program.